New Indicators of Myocardial Work in Healthy Individuals - V. E. Oleynikov; A. V. Babina; V. A. Galimskaya; A. V. Golubeva; K. N. Makarova; N. A. Donetskaya (Рациональная фармакотерапия в кардиологии)
Aim. To study in healthy individuals the gender and age characteristics of left ventricular (LV) myocardial work indicators, their correlations with global LV deformity indicators and echocardiographic parameters characterizing LV systolic and diastolic functions.Materials and methods. 70 Healthy individuals (n=70; 34 men and 36 women; aged 39.3±8.9 years) were included in the study. The echocardiographic examination determined the standard parameters and indicators of myocardial work: global work efficiency (GWE), global constructive work (GCW), global wasted work (GWW), global myocardial work index (GWI); as well as the myocardium deformation characteristics: global longitudinal deformation (GLS), global radial deformation (GRS) and global circular deformation (GCS). Spearman's correlation coefficient was used to investigate the relationship between parameters. A correlation was considered weak at r≤0.3, moderate at 0.3<r<0.7, and strong at r≥0.7.Results. The average value of global work efficiency (GWE) in men was 97% (96; 98), in women – 98% (97; 98). Global constructive work (GCW) in men was 2343.8±350.4 mm Hg%, in women – 2362.2±343.8 mm Hg%. The average value of global wasted work (GWW) in men was 46 mm Hg% (27; 75), in women – 44 mm Hg% (33; 55.5). The global myocardial work index (GWI) in men was 2069.9±356.4 mm Hg%, in women – 2055.7±339.9 mm Hg%. No significant differences were found in the comparative analysis of performance indicators. The analysis of correlations found that the myocardial work indicators didn't have significant correlations with age. Ejection fraction was moderately correlated with GWI (r=0.45) and GCW (r=0.49). Global longitudinal strain was strongly correlated with GWI (r=0.77) and GCW (r=0.77). Global radial strain correlated moderately directly with GWI (r=0.4) and GCW (r=0.4). Global circular strain was moderately correlated with GCW (r=0.35). A strong negative correlation was found between the GWE indicator and the post systolic contraction index (PSI) (r=-0.85). At the same time, PSI and GWW had a strong positive correlation (r=0.85).Conclusion. Indicators of LV myocardial work in healthy individuals do not have gender differences. The efficiency of the work of the myocardium depends primarily on the deformation of the LV, while the constructive work is determined by the volume characteristics. The wasted work indicator depends on the number of segments that peak in the post-systolic period.